2005
DOI: 10.1107/s0108768105000455
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of the stable anhydrous phase of α-lactose from X-ray powder diffraction

Abstract: The stable anhydrous form of alpha-lactose has been obtained by the dehydration of alpha-lactose monohydrate in methanol. An X-ray powder diffraction pattern was recorded at room temperature with a laboratory diffractometer equipped with an INEL curved sensitive detector CPS120. The starting structural model of this form was found by a Monte-Carlo simulated annealing method. The structure was obtained through Rietveld refinements and the minimization of crystalline energy for the localization of the H atoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…Four structures out of these five crystalline forms were solved: single-crystal X-ray diffraction was used for L-H 2 O (Fries et al, 1971;Beevers & Hansen, 1971;Noordik et al, 1984) and L (Hirotsu & Shimada, 1974). Recently we have been able to solve the structure of L H (Platteau et al, 2004) and L S (Platteau et al, 2005) using Xray powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Four structures out of these five crystalline forms were solved: single-crystal X-ray diffraction was used for L-H 2 O (Fries et al, 1971;Beevers & Hansen, 1971;Noordik et al, 1984) and L (Hirotsu & Shimada, 1974). Recently we have been able to solve the structure of L H (Platteau et al, 2004) and L S (Platteau et al, 2005) using Xray powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…It now appears that a number of studies, assessing the internal dynamics of ternary complex of sugar–water–protein and glycerol–water–protein, may have begun to untangle the mechanistic features that relate matrix dynamics and thermal stability to the individual protein molecule dynamics and stability . Through various biophysical studies, the emerging narrative is an emphasis on hydrogen‐bonding networks coupling the matrix dynamics to the internal dynamics of proteins . Many different types of proteins have been analyzed in the various biophysical studies, but the research conducted with heme proteins have built upon the earlier and seminal biophysical work on internal dynamics conducted with myoglobin and other gaseous ligand carriers.…”
Section: Stabilization In Hydrated Disaccharide Mixtures Hydrogen‐bomentioning
confidence: 99%
“…10,41,92,95,[120][121][122] Through various biophysical studies, the emerging narrative is an emphasis on hydrogen-bonding networks coupling the matrix dynamics to the internal dy-namics of proteins. 4, 64,[122][123][124] Many different types of proteins have been analyzed in the various biophysical studies, but the research conducted with heme proteins have built upon the earlier and seminal biophysical work on internal dynamics conducted with myoglobin and other gaseous ligand carriers. In particular, molecular dynamics simulation and Fourier transform infrared spectroscopic analyses of carbon monoxidebound myoglobin(MbCO)-sugar-water systems have revealed that the protein is confined within a network of hydrogen bonds connecting features of the protein surface with water and sugar molecules, and suggesting that this assembly plays a significant role in coupling the individual protein and matrix dynamics to one another.…”
Section: Stabilization In Hydrated Disaccharide Mixtures Hydrogen-bomentioning
confidence: 99%
“…Studies into the water solvatomorphism of several excipient materials have been reported. The structure of the stable anhydrous phase of α‐lactose has been determined from X‐ray powder diffraction data 132. Thermally stimulated depolarization current and differential scanning calorimetry techniques have been used to study the molecular mobility of raffinose in its crystalline pentahydrate and amorphous anhydrous forms 133.…”
Section: Structural Characterization and Properties Of Polymorphs Andmentioning
confidence: 99%